2007
DOI: 10.1098/rsbl.2007.0513
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and non-aggressive personalities differ in oxidative status in selected lines of mice ( Mus musculus )

Abstract: Mice selected for aggression and coping (long attack latency (LAL), reactive coping strategy; short attack latency (SAL), pro-active coping strategy) are a useful model for studying the physiological background of animal personalities. These mice also show a differential stress responsiveness, especially in terms of hypothalamic-pituitary-adrenal axis reactivity, to various challenges. Since the stress response can increase the production of reactive oxygen species, we predicted that the basic oxidative status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 30 publications
3
50
1
Order By: Relevance
“…Here, we show that digesting a meal has a minimal impact on antioxidant capacity, which increased by 4% -less than differences due to forced locomotion (Costantini et al, 2008b), genetic selection for aggression (Costantini et al, 2008a), or natural variation among populations (Costantini et al, 2009). However, the OXY test does not capture all aspects of antioxidant status of the individual (Sepp et al, 2012), and it is possible that other antioxidant defenses were modulated in ways that we did not detect.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that digesting a meal has a minimal impact on antioxidant capacity, which increased by 4% -less than differences due to forced locomotion (Costantini et al, 2008b), genetic selection for aggression (Costantini et al, 2008a), or natural variation among populations (Costantini et al, 2009). However, the OXY test does not capture all aspects of antioxidant status of the individual (Sepp et al, 2012), and it is possible that other antioxidant defenses were modulated in ways that we did not detect.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is recent work by Costantini and colleagues (Costantini et al, 2008a), which showed that mice from strains characterised by a long attack latency ('LAL', i.e. passive personality types) had higher antioxidant capacity than mice from strains with relatively short attack latencies ('SAL', i.e.…”
Section: Introductionmentioning
confidence: 93%
“…First, longevity varies with personality (Cavigelli and McClintock, 2003;Cavigelli et al, 2009;Ewalds-Kwist and Selander, 1996), suggesting a cumulative cost to personality. In LAL-SAL mice for example, young LAL mice have a higher antioxidant capacity than SAL mice yet their oxidative stress levels are not lower, and ultimately they have shorter life spans (Costantini et al, 2008a;Ewalds-Kwist and Selander, 1996). To achieve the same level of oxidative stress, therefore, young LAL mice may up-regulate their antioxidant system, an additional investment that may be costly in later life (Costantini et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations